2019
DOI: 10.47291/efi.v65i1.606
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality, Regional Development, and Internal Migration in Indonesia

Abstract: This study aims to probe the determinants of inter-provincial migration flows in Indonesia and how economic and development changes affect migration patterns. We employ three census periods, 1990, 2000, and 2010. Our study finds that an increase in relative inequality between origin and destination provinces decreases inter-provincial migration and relatively high distance elasticity in Indonesia leads to high migration cost. People are more inclined to migrate due to push factors as opposed to pull factors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…These arguments have been supported by BPS -Statistics Indonesia, which found that the percentage of unmet healthcare services needs on Java is significantly below the national average from 2018 to 2020. In addition, Prima and Khoirunurrofik (2019) found that the provision of public goods affected the flow of people living in less developed areas. Consequently, this causes productive-age adults to move to the more concentrated area either for work or to gain better educational access.…”
Section: Discussionmentioning
confidence: 99%
“…These arguments have been supported by BPS -Statistics Indonesia, which found that the percentage of unmet healthcare services needs on Java is significantly below the national average from 2018 to 2020. In addition, Prima and Khoirunurrofik (2019) found that the provision of public goods affected the flow of people living in less developed areas. Consequently, this causes productive-age adults to move to the more concentrated area either for work or to gain better educational access.…”
Section: Discussionmentioning
confidence: 99%
“…Technically, migration results from interactions among multiple driving aspects, including factors associated with origin and destination, physical/non-physical intervening obstacles, and subtle personal aspects (Lee 1966). In the literature, scholars often use economic approaches to understand human mobility (Castelli 2018;Marta et al 2020;Prima and Khoirunurrofik 2019;Todaro 1969); however, studies on personal behavior in rural mobility are arising (Dandy et al 2019;Pedersen 2018). Of the emerging behavioral research, studies on place attachment have recognized personal behavior as a contributing factor to rural migration along with its complexity (Barcus and Brunn 2009).…”
Section: Rural Emigration and Place Attachmentmentioning
confidence: 99%
“…Berdasarkan kajian literatur, penelitian yang ada belum membahas tentang adanya perubahan pola migrasi pada saat pelaksanaan pilkada khususnya di negara demokrasi muda seperti Indonesia. Pada penelitian terdahulu terkait migrasi (Prima & Khoirunurrofik, 2019;Tiwari, 2017;Wajdi et al, 2015;, belum ditemukan adanya penelitian yang menghubungkan desentralisasi khususnya waktu pelaksanaan pilkada sebagai salah satu faktor yang mungkin memengaruhi perubahan pola migrasi di Indonesia. Selain itu, belum ditemukan adanya penelitian yang menganalisis migrasi secara agregat pada level kabupaten/kota dengan menggunakan data migrasi per semester.…”
Section: Gambar 1 Persentase Penduduk Yang Melakukan Migrasi DI Indon...unclassified